(3eQTO GdeJCgds - (3eMeO Hf bWH GdOjf GdCRfjbis
(3ChdgG (B:s
(3hHYO adeG QCjJ fSGA GdReGf jJRjf HRi GdaGMTGJ hjeTjf ai GdCShGb (B,(3SejJg HeQTO GdeJCgd hLYdJg eTJedkG Ydi CMO YTQ aUdkG s
(3BNQgG (B:s
(3Gddge CQMe LejY GdeDefjf hGdeDefGJ hGdeSdejf hGdeSdeGJ hUdi Gddg Ydi LejY GdCfHjGA hGdeQSdjf hGdMeO ddg QH GdYGdejf GfJgi HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1655s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs